Successfulness of general and special physical qualities’ development on different stage of students-boxers’ training - A.V. Gaskov; A. V. Kuzmin; D. M. Kudryavtsev; S. S. Iermakov (Physical Education of Students)
Purpose: to study indicators of general and special physical condition on different stages of macro-cycle training. Material: in testing qualified boxers - 28 sportsmen - participated. Characteristics of general and special fitness were registered. Results: it was found that structure of general and special physical qualities can be described by 9 factors, explaining about 80% of total sample variance. It was also determined that factorial structure of general and special physical fitness indicators does not change depending on stages of trainings. At every of the tested stages the marked out factors do not depend on each other. These factors are separate necessary sides of training. It was found that on general preparation stage of training these factors characterize sides of fitness: effectiveness of punches of strong and weak arms; special speed and power endurance; general endurance and strength of muscles (hands’ flexors); specific sensor-motor reaction; condition of upper girdle muscles; general speed and power endurance; speed of punch movement. Conclusions: when distributing training means and loads it is necessary to uniformly doze correlation of means for all marked out factors. It ensures growth of boxers’ spots results.